Impact of reference diet composition on apparent digestibility coefficients of two protein-rich ingredients in Nile tilapia - Maria Fernanda Oliveira da Silva; Rafael de Souza Romaneli; Luis Felipe Mussoi; Karthik Masagounder; Débora Machado Fracalossi (Scientia Agricola, 2023)
ABSTRACT Protein quality is related to amino acid composition and digestibility. Accurate evaluation of apparent digestibility coefficients (ADCs) of nutrients in commonly used feedstuffs is paramount for formulating efficient aquafeed. ADCs of soybean meal (SBM) and poultry by-product meal (PBM) were evaluated using reference diets formulated with two types of ingredients (semi-purified [SP] and practical [P]) for juvenile Nile tilapia ( Oreochromis niloticus, Linnaeus) of the GIFT strain. Groups of 20 juveniles (65.05 ± 12.37 g) were fed twice a day to apparent satiety with one of the four experimental diets (SBM-SP, SBM-P, PBM-SP, and PBM-P) in quadruplicate for 30 days. After the last feeding, feces were collected by siphoning hourly and the ADCs of dry matter, protein, and amino acids (AAs) were calculated. Nile tilapia exhibited a high capacity to digest SBM and PBM, with most ADCs exceeding 90 %. The type of reference diet affected the ADCs of protein and AAs on the test ingredients, with the SP reference diet providing the highest ADC, mainly in SBM. Digestibility data generated with a P-type reference diet demonstrated more practical relevance than those generated with an SP-type reference diet. They can be applied in digestibility studies for Nile tilapia.